Scarcity in todays consumer markets: scoping the research landscape by author keywords - Haoye Sun; Thorsten Teichert (Management Review Quarterly, 2022)
Scarcity refers to not having enough of what one needs. This phenomenon has shaped individuals life since ancient times, nowadays ranging from daily-life scarcity cues in shopping scenarios to the planet's resources scarcity to meet the worlds consumer demand. Because of this ubiquity of scarcity, the topic has been attracting attention from scholars and practitioners in different areas. Studies regarding scarcity were conducted across disciplines, based on different assumptions, and focused on distinct study subjects. A lack of mainstream about this topic hindered the convergence of core ideas among different schools of thought. In this article, we take an integrative socio-economic perspective to join diverse findings on scarcity affecting consumer markets, identify topic-specific research questions still to be answered, and provide suggestions for future and integrative research opportunities. A systematic review based on author keywords from 855 publications analyzing scarcity affecting business-consumer interactions serves as a database. Exploratory factor analyses based on author keywords identify shared patterns within and linkages across discourses stemming from various disciplines and theories. Results differentiate distinct research foci in the consumer behavior, socio-political, and other disciplinary research realms. A mapping of these research themes identifies the scarcity-related interplay among consumers, producers, and other stakeholders. Findings point out research directions for future studies at both the research realm level and the interdisciplinary level.
Keywords: M00; Q00; 650; Scarcity; Author keywords; Research streams; Consumer behavior; Socio-political